ORGANIZATIONAL CAPACITY FOR LEARNERS: LET THEM ALL SPEAK AND WRITE - Bulelwa Makena (International Journal of Innovative Technologies in Social Science, 2023)
In classroom situations encouraging learners to holistically engage in spoken and written tasks in English language learning with characteristics of being additional and unfamiliar, is equated to enhancing learning environment, thereby fostering individual and collective growth. For organizations to inspire recipients with speaking and writing abilities, this leads to innovative solutions. This paper seeks to inquire whether fostering opportunities in an organizational capacity for learners to engage in speaking and written activities have any significant importance towards enhanced language development. Underpinning this inquiry is a qualitative research approach with a case study design to explore key characteristics of the studied case. To gather data, five conveniently nominated participants were identified from a rurally located institution of higher learning. Semi-structured interviews led to a thematic analysis of gathered data. Findings revealed that through consistent engagements in spoken and written texts (i) there were improved communication skills and (ii) the development of an inclusive learning environment. The study concludes that when learner communication skills have been refined, this is tantamount to academic excellence with recommendations that individual learner contributions should be valued as inclusion promotes mutual responsiveness among teachers and learners not only in language learning but across all subjects underpinning curriculum.